2, 7-Di-tert-butyl-9, 9′(10H, 10′H)-spirobiacridine-10, 10′-dioxyl as a ground triplet biradical: The role of tert-butylation. Issue 43 (22nd October 2020) - Ichihashi, Kana; Kanetomo, Takuya; Enomoto, Masaya; Ishida, Takayuki
Graphical abstract: Highlights: A new compound, doubly tert -butylated spirobiradical. Intramolecular ferromagnetic interaction with 2 J / k B = +22.3(5) K. Longer intermolecular O…O distances than those of non- tert -butylated compound. tert -Butylation as a useful method to reduce the intermolecular interaction. Abstract: The synthesis of a doubly tert -butylated spirobiradical, 2, 7-di- tert -butyl-9, 9′(10 H, 10′ H )-spirobiacridine-10, 10′-dioxyl is reported. The X-ray diffraction study clarified that the two dihydroacridine skeletons were fused at the sp 3 -carbon atom affording a cruciform structure. The frozen-solution electron spin resonance spectrum showed a typical zero-field-splitting pattern. The magnetic study revealed the presence of an intramolecular ferromagnetic interaction with 2 J / k B = +22.3(5) K. The density-functional-theory calculation results are entirely consistent with the experimental results. After comparison with the known unsubstituted spirobiradical, we can conclude that tert -butylation is a useful method to reduce the intermolecular interaction without breaking the degeneracy of the singly occupied molecular orbitals.